Exploring what works well and less well in a community-based drop-in hub providing health and wellbeing services for people experiencing homelessness: a participatory action evaluation of service coordination - Emma A. Adams; Sheena E. Ramsay (BMC, 2024)
Abstract Background People experiencing homelessness often face obstacles accessing health and social care support. Challenges are further exacerbated when support provision for multiple unmet needs are not integrated or coordinated. To overcome these challenges, there has been growing attention on integrating and co-locating health and wellbeing services for people experiencing homelessness. In an urban area of North East England, a long-standing Hub or 'drop-in centre' offers a range of health and wellbeing support by bringing together the different health and care system agencies in one space. However, little is known about the perspectives of providers on what works well and less well in how the different services are coordinated. Methods Using a participatory action research approach, a qualitative service evaluation was undertaken between June and September 2023. Fourteen interviews were conducted with providers who work in a paid or voluntary capacity operating some of their service offerings or support in the Hub. Interview transcripts were analysed using inductive reflexive thematic analysis. Results Three themes were evident from the evaluation: 1) location and space matter, 2) co-location and relationships make a difference, and 3) service consistency and flexibility are paramount. Conclusion Co-locating support to cover the breadth of health and care needs has the potential to increase engagement and access for people experiencing homelessness, and to enhance trust with service users and between agencies. This model provides a unique example of co-location and integration of support, particularly with it being operated by a community housing organisation.